Phonological Structure of Kaili Language Rai Dialect - Nur Alya Amandah; Siti Masyita Islamiya; Kristina Sandipu; Lili Indriani (Global Education Journal, 2026)
The main problems studied are the form of phonological processes as well as the variations and sound characteristics of language used in daily communication. This study aims to analyze phonological processes and identify the dominant types of sound changes in the Kaili language of the Rai dialect. The method used in this study is qualitative descriptive. The research data is in the form of oral speech (words, phrases, and sentences) obtained directly from native speaker informants through the simak method (tapping technique, simak engaged cakap, simak free engaged cakap, and note) and cakap method (fishing technique, recording, and note). Data analysis is carried out interactively, which includes the data reduction stage, data presentation in the form of inventory tables and descriptions, and conclusion drawn. The results show that there is a variety of vowel phonemes (/a/, /i/, /u/, /e/, /o/) and various consonant phonemes, noting that the consonant phoneme /w/ is not found in this dialect. The sound system of the Kaili language of the Rai dialect has unique characteristics that are shown through the presence of contrasting consonants (such as the pairs /p/ and /b/, /k/ and /g/), front and middle consonant clusters (e.g. mpu'u, rombi), consonant sequences (punti, komporo), and diphthongs (/ai/, /au/, /oi/). In addition, a consistent pattern of sound distribution was found, including contrast distributions that function to distinguish the meaning of words (e.g. the vowels /u/ and /o/ in the word pulu polo) as well as complementary distributions influenced by the phonological environment around the phoneme.